Bimetallic oxide nanoparticles contained hollow spheres with sodium as a core: a promising energy storage advanced structure. (December 2022) - Parvin, N.; Dhananjaya, M.; Mandal, T.K.; Joo, S.W.
Abstract: The bimetallic oxide nanoparticles as outer shell with sodium entrapped as a core part of a hollow porous core–shell (HoPoCs) can be a promising battery electrode composition. Till now, scientists are struggling to synthesize ternary metal oxide hollow spheres due to the reactions between diverse cations and anions of different metal precursors. Also, the extremely reactive character of sodium prevents it from remaining alone without compound formation is unveiled. Here for the first time, we entrapped sodium and synthesized bimetallic nanoparticles contained outer shell hollowsphere (Na@ZnO@MoO2 ) successfully by sorption (absorption + adsorption) of two metal precursors (sodium molybdate dihydrate and zinc chloride) in two steps without adding any reaction inhibiting agent. As a result, significantly Na is entrapped as a core and ZnO and MoO2 nanoparticles forming the outer shell of the sphere. 'Na' entrapment is confirmed by X-ray photoelectron spectroscopy and high-angle annular dark-field scanning transmission electron microscopy elemental mapping. We employed our sodium entrapped HoPoCs bimetallic oxide nanoparticles sphere (Na@ZnO@MoO2 ) as a battery anode getting advantages from their structural specialty shows excellent battery properties promising for application in energy storage technologies. The initial specific capacity of these HoPoCs-Na@ZnO@MoO2 sphere is 940 mAh/g (1C), with exceptional stability (790 mAh/g) after 1000 cycles at a current density of 2C) and excellent rate capability. This approach will motivate the synthesis of other superior reactive element entrapped core–shell metal oxides for next-generation rechargeable batteries and other advanced suitable applications like microreactor, protector of explosive materials, and so on. Highlights: Sodium entrapped and protected from highly oxidation. The porous core–shell ternary metal oxide hollow spheres synthesis by two-step sorption procedure. Cost-effective and safe nature of the material encourage hollow spheres uses in large-scale energy storage system. This method could open a new era to protect the environment by using explosive materials for mankind.